Massive thymic hemorrhage and hemothorax occurring in utero. Issue 1 (December 2015) - Gargano, Giancarlo; Paltrinieri, Anna; Gallo, Claudio; Di Pancrazio, Luciana; Roversi, Maria; Ferrari, Fabrizio
Abstract Background Thymic enlargement is a common and physiological finding in children and neonates' X-rays, but it is usually asymptomatic. Occasionally it can cause respiratory distress. In most cases the aetiology of this expansion remains unclear and it is diagnosed as a thymic hyperplasia. True thymic hyperplasia is defined as a gland expansion, both in size and weight, while maintaining normal microscopic architecture. Often it is a diagnosis of exclusion and prognosis is good. Thymic haemorrhage is an unusual condition related to high foetal and neonatal mortality. Case Presentation We report a case of spontaneous massive thymic haemorrhage in a newborn developing at birth acute respiratory distress associated with severe bilateral haemothorax. Thymic enlargement was evident after pleural evacuation and confirmed by radiographic, Computed Tomography (CT) images and Magnetic Resonance Imaging (MRI) sequences. The spontaneous resolution of this enlargement seen with CT scan and MRI sequences suggested a thymic haemorrhage; surgery was not necessary. Conclusion Thymic haemorrhage should be considered in newborn infants with pleural effusion, mediastinal space enlargement and Respiratory Distress.